Hubungan Antara Self Efficacy dengan Stres Akademik pada Siswa Kelas XI Di SMAN 4 Pandeglang dan Implikasi dalam Layanan Bimbingan dan Konseling - Julianti Aprilia; Vasco Delano; Devi Nurul Fikriyani (JCOSE Jurnal Bimbingan dan Konseling, 2025)
Academic stress is a common issue among high school students, particularly when facing heavy academic demands. One crucial factor that can help reduce academic stress is self-efficacy, defined as an individual’s belief in their ability to complete tasks and overcome challenges. This study aims to examine the relationship between self-efficacy and academic stress among eleventh-grade students at SMAN 4 Pandeglang and its implications for guidance and counseling services. The research employed a quantitative method with a correlational design. The population consisted of 456 eleventh-grade students, while the sample comprised 213 students selected using simple random sampling. The instruments used were self-efficacy and academic stress questionnaires that had been tested for validity and reliability. Data were analyzed using the Product Moment Correlation (Pearson Correlation). The results revealed a significant negative relationship between self-efficacy and academic stress, with a correlation coefficient of r = -0.776 and a significance level of 0.000 < 0.05. This indicates that the higher the students’ self-efficacy, the lower their academic stress. These findings highlight the importance of guidance and counseling services, particularly group guidance, in fostering students’ self-efficacy so they can manage academic stress more effectively.